Performance of anodic recirculation by a variable flow ejector for a solid oxide fuel cell system under partial loads. (20th March 2020) - Baba, Soumei; Takahashi, Sanyo; Kobayashi, Nariyoshi; Hirano, Satoshi
Abstract: An anode gas recycle (AGR) system driven by a variable flow rate ejector was developed for use in small-scale solid oxide fuel cell (SOFC) systems. The partial load conditions were simulated through recycling power generation experiments to clarify the fundamental characteristics of the variable flow ejector by using actual 1 kW-class SOFC equipment at the steady state. We achieved power generation in a range of recirculation ratios under partial load conditions of 62.5%–80% by controlling the recirculation characteristics with the developed ejector by using a needle. Results showed that the recirculation ratio can be controlled in the range of 0.595–0.694 by adjusting the driving energy with the ejector even at a partial load where the fuel gas flow rate of the ejector changes. Furthermore, the effect of the recirculation ratio on SOFC output was discussed based on the results of gas analyses and temperature measurements. As the recirculation ratio increased, the fuel concentration at the SOFC inlet decreased and the water vapor concentration increased. However, the effect of the recirculation ratio on the stack temperature and output power was proposed to be small. In addition, it was confirmed that the operation was performed under safe conditions where no carbon deposition occurred by circulating the steam generated inside the SOFC without an external water supply. Ejector characteristics during power generation experiments were lower than those at room temperature, which indicates that an ejector upstream pressure of approximately 20–170 kPa gauge pressure was required. Variations in the fluid properties of the driver gas in the ejector motive nozzle heated by the hot suction gas were found to degrade the performance of the ejector installed in the SOFC system, as compared with the results of simulation experiments at room temperature. Nevertheless, the recirculation ratio range required for operation could be satisfied by adjusting the flow velocity of the driving gas through needle control. Highlights: 1 kW SOFC with anode gas recycle driven by a variable flow ejector is presented. Partial load tests using methane fuel are performed without external water supply. The recirculation ratio can be controlled in the range of 0.595–0.694. Stable output power with self-supplied steam can be obtained. The performance of the variable flow ejector is evaluated.